Монголчуудын зарга тэмцлийг зүйр цэцэн үгсээр мөшгин үзсэн нь: (Түүхийн социологийн судалгаа) - Ч.Тамир; Р.Төрдалай (Acta Mongolica, 2007)
The article about the Mongolians petition. This study analyzed content of proverb about petition. The study illustrated in the content analyses, based historical origins of petition in traditional Mongolian society. The petition as form (legitimize) political participation of Mongolian Life.